Inventing Idaho : the Gem State's eccentric shape - Petersen, Keith C., 1951- (Washington State University Press, 2022)
"As Idaho's State Historian, the question author Keith C. Petersen heard most was, "How did Idaho get such a strange shape?" In this book, he answers that popular inquiry, breaking the state's intriguing border story into six sections covering the fascinating events and people involved in creating the peculiar borders-boundaries that have held enormous influence on much of Idaho's political, economic, and cultural history"--